2002
DOI: 10.1038/sj.bjc.6600600
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy postponement and childlessness leads to chronic hypervascularity of the breasts and cancer risk

Abstract: Epidemiologists have established that women with small families, and particularly nulliparae, are prone to develop breast cancer later in life. We report that physiological mammary hypervascularity may be an intermediate reason against the background that breast-core vascularity is normal in pregnancy but pathological in the vascularisation of cancer. We examined breast 'core' vascularity in nulliparae during their potential reproductive life and in parous women after their last birth but before their menopaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Mammary gland development can be divided into seven stages: embryonic, postnatal, juvenile, puberty, pregnancy, lactation, and involution. One of the leading risk factors for breast cancer is nullparity [ 51 ]. Hence, the delineation of factors that regulate lactogenesis (terminal differentiation) is important in understanding the etiology of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mammary gland development can be divided into seven stages: embryonic, postnatal, juvenile, puberty, pregnancy, lactation, and involution. One of the leading risk factors for breast cancer is nullparity [ 51 ]. Hence, the delineation of factors that regulate lactogenesis (terminal differentiation) is important in understanding the etiology of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 The risk of breast cancer is also influenced by pregnancy, where nulliparity and late age at first birth both increase the lifetime incidence of breast cancer. 43,44 An increased risk of breast cancer has been shown in women exposed to moderate to high levels of ionizing radiation, including women treated with radiotherapy towards the thoracic region, 45 and among survivors of the nuclear bombings in Japan. 46 A number of studies have evaluated the influence of tobacco smoking in breast cancer, and the data do not support any important relation.…”
Section: What Causes Breast Cancer?mentioning
confidence: 99%
“…Research has shown that women who have their first child in their 30s are 63% more likely to develop breast cancer before menopause and 35% more likely to develop the disease after menopause than their counterparts who give birth to their first child before the age of 22. Women who remain childless have an even higher risk (Simpson et al 2002). The potential for a link between ACM rates for breast cancer and differences in family planning between former East and West Germany is therefore worthy of future analysis.…”
Section: Discussionmentioning
confidence: 96%